Macroeconomic Implications of Money Laundering - Quirk, Peter (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews the main analytical, empirical, and policy issues related to the macroeconomic implications of money laundering. The paper discusses, first, how money laundering can be measured, given that it is unobservable, and reports cross-section econometric estimates of the displacement of monetary behavior in industrial countries attributed to money laundering. It then examines the various potential channels by which money laundering influences macroeconomic performance, including an econometric estimate of its effects on GDP growth rates. Finally, the paper discusses macropolicy implications, particularly in the areas of exchange controls, prudential banking supervision, tax evasion, statistical reporting, and legislation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet